Pathobiochemical signatures of cholestatic liver disease in bile duct ligated mice - Abshagen, Kerstin; Ebert, Matthias; Weng, Honglei; Dooley, Steven (BMC systems biology, 2015)
Disrupted bile secretion leads to liver damage characterized by inflammation, fibrosis, eventually cirrhosis, and hepatocellular cancer. As obstructive cholestasis often progresses insidiously, markers for the diagnosis and staging of the disease are urgently needed. To this end, we compiled a comprehensive data set of serum markers, histological parameters and transcript profiles at 8 time points of disease progression after bile duct ligation (BDL) in mice, aiming at identifying a set of parameters that could be used as robust biomarkers for transition of different disease progression phases.
Gesehen am 18.12.2017